Parent and teacher perspectives on psychological adjustment: A national measurement study in Trinidad and Tobago. Issue 2 (3rd April 2017) - Drogalis, Anna Rhoad; McDermott, Paul A.; Watkins, Marley W.; Chao, Jessica L.; Worrell, Frank C.; Hall, Tracey E.
Abstract : This article reports on the national standardization and psychometric properties of the Adjustment Scales for Children and Adolescents–Home Edition (ASCA-H) for use in Trinidad and Tobago. ASCA-H is a parent rating scale composed of behavioral indicators in play, social, and learning contexts. The sample was comprised of students ( N  = 780) attending government and assisted elementary schools. Exploratory and confirmatory factor analyses revealed two internally consistent dimensions, Problems in Contexts Requiring Disciplined Behavior (i.e., Indiscipline) and Problems in Contexts Requiring Engaged Behavior (i.e., Disengagement). Dimensions were scaled with IRT and Bayesian scoring methods, with Disengagement scores more strongly relating to clinical disturbances, peer contexts, and classroom learning contexts. The norming information on the ASCA-H will enable identification of at-risk students and allow resources to be targeted to specific situational contexts with parents and other adults.